Bone mesenchymal stem cell-derived exosomal miR-26a-3p promotes autophagy to attenuate LPS-induced apoptosis and inflammation in pulmonary microvascular endothelial cells: BMSC-expos on ALI - Wang, Qianfei; Huang, Yiming; Fu, Zherui (Cellular and Molecular Biology, 2024)
Acute lung injury (ALI) is a serious lung disease. The apoptosis and inflammation of pulmonary microvascular endothelial cells (PMVECs) are the primary reasons for ALI. This study aimed to explore the treatment effect and regulatory mechanism of bone mesenchymal stem cell-derived exosomes (BMSC-expos) on ALI. PMVECs were stimulated by Lipopolysaccharide (LPS) to imitate ALI environment. Cell viability was determined by CCK-8 assay. Cell apoptosis was evaluated by TUNEL and flow cytometry. ELISA was utilized for testing the contents of TNF-α, IL-1β, IL-6, and IL-17. Western blot was applied for testing the levels of autophagy-related proteins LC3, p62, and Beclin-1. RNA interaction was determined by luciferase reporter assay. The ALI rat model was established by intratracheal injection of LPS. Evans blue staining was utilized for detecting pulmonary vascular permeability. Our results showed that LPS stimulation notably reduced cell viability, increased cell apoptosis rate, and enhanced the contents of inflammatory factors in PMVECs. However, BMSC-exo treatment significantly abolished the promoting effects of LPS on cell injury. In addition, we discovered that BMSC-exo treatment notably activated autophagy in LPS-induced PMVECs. Furthermore, BMSC-expos upregulated miR-26a-3p expression and downregulated PTEN in PMVECs. MiR-26a-3p was directly bound to PTEN. MiR-26a-3p overexpression reduced cell apoptosis, and inflammation and promoted autophagy by silencing PTEN. Animal experiments proved that miR-26a-3p overexpression effectively improved LPS-induced lung injury in rats. The results proved that BMSC-expos promotes autophagy to attenuate LPS-induced apoptosis and inflammation in pulmonary microvascular endothelial cells via miR-26a-3p/PTEN axis.